Managing Flood Risk Innovative Approaches from Big Floodplain Rivers and Urban Streams (Springer International Publishing, 2018)
The past half century has seen an evolution in thinking from 'flood control' to 'flood risk management', recognizing that risk results from both hazard and vulnerability. Rather than rely only on engineering structures to reduce flood magnitude or extent, recent policies emphasize avoiding construction in flood-prone areas (or moving people from floodplains), reducing impacts on exposed populations through early warning systems, and insurance to aid in recovery. Implementing this new approach faces many challenges but also offers opportunities for synergies, as described in this book for a range of large floodplain rivers and smaller urban streams across North America and Europe. This book is unique in presenting the voices of those on the front lines of implementing a new paradigm in flood risk management, each river with a unique set of challenges and opportunities derived from its specific geography as well as differences in governance between the American and European contexts. .